Management of Oral Leukoplakia: A Review - Sadat, S M Anwar; Tajin, Fariha; Nishi, Nowrin Jahan; Islam, Naimul (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Oral leukoplakia is a widely known white oral mucosal lesion which is encountered by dental practitioners specially by oral and maxillofacial surgeons in daily practice. The objective of this article is to update the reader on the concept of treatment algorithm for the management of leukoplakia. Articles were searched through PubMed, Google Scholar and the Cochrane Library (2017 to 2021), confining search to English language with the key words e.g., leukoplakia, white patch, precancerous lesion, premalignant lesion and oral potentially malignant disorders. After initial collection of abstracts of 78 articles, finally 24 papers have been selected for writing up the paper updating on clinico-pathologic characters, diagnosis, evaluation, risk of malignant transformation, management and prognosis of oral leukoplakia. Oral leukoplakia is a common oral potentially malignant disorder. Early diagnosis and screening for oral cancer can potentially subside the mortality and morbidity of disease. Incisional biopsy is mandatory for diagnosis, treatment planning and for checking the prognosis of the lesion. There are no universal modalities on the most appropriate treatment, and despite the treatment disease can recur and undergo malignant transformation in patients. For high-risk lesions, complete excision is recommended and clinician should closely follow up these patients for life. For low-risk lesions and successfully treated cases, routine check-up is recommended by dental practitioners. Health education, counselling the individual, and behavioral therapies are most essential methods of prevention at a primary level by every health care provider. J Bangladesh Coll Phys Surg 2023; 41: 156-163